2016
DOI: 10.1038/jes.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of radio frequency electromagnetic field exposure levels in outdoor environment and comparing with reference levels for general public health

Abstract: In this study, radio frequency electromagnetic field exposure levels were measured on the main streets in the city center of Diyarbakır, Turkey. Measured electric field levels were plotted on satellite imagery of Diyarbakır and were compared with exposure guidelines published by the International Commission on Non-Ionizing Radiation Protection (ICNIRP). Exposure measurements were performed in dense urban, urban and suburban areas each day for 7 consecutive days. The measurement system consisted of high precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Nuestro estudio cuenta además con mediciones interiores que se realizaron tomando como fuentes emisoras de RF-CEM las provenientes de computadoras personales y de fuentes de iluminación. A diferencia del trabajo publicado por Cansiz M en nuestro estudio las mediciones se realizaron en una sola instancia, sin evaluar las posibles modificaciones a lo largo de un día completo (7).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nuestro estudio cuenta además con mediciones interiores que se realizaron tomando como fuentes emisoras de RF-CEM las provenientes de computadoras personales y de fuentes de iluminación. A diferencia del trabajo publicado por Cansiz M en nuestro estudio las mediciones se realizaron en una sola instancia, sin evaluar las posibles modificaciones a lo largo de un día completo (7).…”
Section: Discussionunclassified
“…(Asunción) / Vol. 51 - Nº 2, 2018 personas potencialmente expuestas si no se controlan adecuadamente (6)(7)(8)(9)(10).…”
Section: Introduccionunclassified
“…[46][47][48] Despite of its continuous availability, radio waves arises concern of EMI/EMC of penetrating through human body; subjected to risk by World Health Organization. [11][12][13][14][15][16]49 At the midst of it, RF energy harvesting 50-53 is still considered as robust, trustworthy and feasible solution for meeting the increasing power requirements of low power embedded devices in both consumer and commercial usage.…”
Section: Rf Fundamentalsmentioning
confidence: 99%
“…The study [17] has reported that health effects of exposure to radiofrequency electromagnetic fields (RF EMF) are a serious concern not only from the users of smart-devices or people who live next to the base stations, but also from government and non-government organizations which are responsible for public health. Other studies [18,19,20] also have indicated that RF EMF affects not just human health but also animal and plant health.…”
Section: Electromagnetic Radiation Effects On Healthmentioning
confidence: 99%